Estimation of technical efficiency of broiler production in Peninsular Malaysia: A stochastic frontier analysis (Journal of Business Management and Accounting, 2012)
This study analyzed the technical efficiency of poultry production in Peninsular Malaysia using the stochastic frontier production function analysis. Time series data were collected for this purpose. The frontier function involved variables such as farm, farmer and economic variables. An econometric technique of the stochastic frontier production function approach was applied whereby technical efficiency was measured together with a systemic inefficiency farm in the inefficiency model. The results showed that during the early period, technical progress was rather slow, but subsequently improved during the second period. This is due to changing structure and labor saving technologies which focus towards modernization of the broiler industry. However several policy reforms are needed to enhance the global competitiveness of Malaysian broiler industries especially pertaining to technology policy. It can be concluded that improved extension linkage to sensitize the producers of the need to use new technology such as close house systems. In addition, the government must boost efforts to produce and develop genetically improved breeds of poultry of a higher feed conversion ratio.